Ioncopy: a novel method for calling copy number alterations in amplicon sequencing data including significance assessment - Budczies, Jan; Pfarr, Nicole; Stenzinger, Albrecht; Treue, Denise; Endris, Volker; Ismaeel, Fakher; Bangemann, Nikola; Blohmer, Jens-Uwe; Dietel, Manfred; Loibl, Sibylle; Klauschen, Frederick; Weichert, Wilko; et al. (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7451 Jan Budczies, Nicole Pfarr, Albrecht Stenzinger, Denise Treue, Volker Endris, Fakher Ismaeel, Nikola Bangemann, Jens-Uwe Blohmer, Manfred Dietel, Sibylle...
Gesehen am 20.02.2020